The Expressive Illocutionary Act Used By The Main Character In â€œPersuasionâ€ Movie - Made Adis Indayanti; Ida Ayu Mela Tustiawati (STKIP AGAMA HINDU SINGARAJA, 2023)
This study analyzes the Attitude of expressive illocutionary acts found in the movie script of